Synthesis of the [(η6-p-cymene)Ru(dppb)Cl]PF6 complex and catalytic activity in the transfer hydrogenation of ketones. Issue 20 (18th October 2017) - Higuera-Padilla, Angel Ruben; Batista, Alzir Azevedo; Colina-Vegas, Legna; Villarreal, Wilmer; Colnago, Luiz Alberto
Abstract: Catalysis under mild conditions is of great importance to various chemistry areas, particularly for the development of novel active compounds and for natural products modifications, among others. In this study, the synthesis, characterization, and evaluation of the catalytic activity of a new ruthenium(II) compound, [(η 6 - p -cymene)Ru(dppb)Cl]PF6 (A ) where dppb=1, 4-bis(diphenylphosphine)butane, is presented. Catalytic activity of the new Ru(II) compound was tested on hydrogen transfer reaction in various substrates, acetophenone, benzophenone, cyclohexanone, and methyl-ethyl-ketone. Potassium hydroxide was used as base, whereas isopropanol served as both solvent and hydrogen source. Samples comprising substrate: base: catalyst at a 200 : 20 : 1 ratio were poured into 5 mm tubes and monitored in situ at 40, 50, and 60 °C in a 600 MHz NMR spectrometer. The complex was active in the transfer hydrogenation of ketones, achieving conversions superior to 90% within 4 h at 60 °C, which suggests under mild conditions. Therefore, in situ monitoring the reactions through 1 H NMR was a valuable technique to establish the possible catalytic mechanism of Ru(II) precatalyst. Abstract :